Region-Specific versus Country-specific Poverty Lines in Analysis of Poverty - Magne Mogstad; Audun Langørgen; Rolf Aaberge (Statistics Norway, Research Department, 2005)
The standard practice in most OECD countries is to measure and evaluate poverty on the basis of a poverty line defined as a specific proportion of the median equivalent income within a country. However, this approach disregards regional differences in prices and needs within a country and may, therefore, provide an incomplete and even an incorrect picture of the extent as well as the geographical and demographical composition of the poor. To account for differences in prices and needs, this paper introduces an alternative method of measuring poverty based on a set of region-specific poverty lines. Applying Norwegian household register data for 2001 we find that the overall extent of poverty is only slightly affected by the change in definition of poverty line. However, the geographical as well as the demographical composition of poverty are shown to depend heavily on whether the method of measuring poverty relies on region-specific or country-specific thresholds. As expected, the results demonstrate that the analysis of poverty based on country-specific thresholds produces downward biased poverty rates in urban areas and upward biased poverty rates in rural areas. Moreover, when region-specific poverty thresholds form the basis of the poverty analysis, we find that the poverty rates among young singles and non-western immigrants are significantly higher than what is suggested by previous empirical evidence based on a joint country-specific poverty line.
Keywords: I32; 330; Measurement of poverty; poverty line; geographical and demographical poverty profile